Mukhamandapa of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The mukhamandapa (front porch) of the Suhaveshwar Temple is built on a trabeated system. The beams of the mukhamandapa connect to the concentric circles of the ceiling. The circular ceiling is made up of concentric circles of cusps. These diminish in size, and the centre is decorated with a suspending floral medallion.